Investigation on absorption cross-section of photosynthetic pigment molecules based on a mechanistic model of the photosynthetic electron flow-light response in C3, C4 species and cyanobacteria grown under various conditions - Ye, Zi-Piao; Stirbet, Alexandrina; An, Ting; Robakowski, Piotr; Kang, Hua-Jing; Yang, Xiao-Long; Wang, Fu-Biao (Frontiers in Plant Science, 2023)
Investigation on intrinsic properties of photosynthetic pigment molecules participating in solar energy absorption and excitation, especially their eigen-absorption cross-section ( ik ) and effective absorption cross-section (  ik ), is important to understand photosynthesis. Here we present the development and application of a new method to determine these parameters, based on a mechanistic model of the photosynthetic electron flow-light response. The analysis with our method of a series of previously collected chlorophyll a fluorescence data show that the absorption cross-section of photosynthetic pigment molecules has different values around 10 −21 m 2 , for several photosynthetic organisms grown under various conditions: (1) the conifer Abies alba Mill., grown under high light or low light; (2) Taxus baccata L., grown under fertilization or non-fertilization conditions; (3) Glycine max L. (Merr.), grown under CO 2 concentration of 400 or 600 mol CO 2 mol −1 in a leaf chamber under shaded condition; (4) Zea mays L., at temperatures of 30 °C or 35 °C in a leaf chamber; (5) Osmanthus fragrans Loureiro, with shaded-leaf or sun-leaf; and (6) the cyanobacterium, grown under two different nitrogen supplies. Our results show that  ik has the same order of magnitude, and   ik for these species decreases with increasing light intensity, demonstrating the operation of a key regulatory mechanism to reduce solar absorption and avoid high light damage. Moreover, compared with other approaches, both  ik and   ik can be more easily estimated by our method, even under various growth conditions (e.g., different light environment, different CO 2 , NO 2 , O 2 and O 3 concentrations, air temperatures, or water stress), regardless of the type of the sample (e.g., dilute, or concentrated cell suspensions, or leaves). Our results also show that CO 2 concentration and temperature have little effect on  ik values for G. max and Z. mays. Consequently, our approach provides a powerful tool to investigate light energy absorption of photosynthetic pigment molecules and gives us new information on how plants and cyanobacteria modify their light harvesting properties under different stress conditions.